Study of factors affecting performance of primary health care workers in a health organization. - De Silva, U.H.S (My University, 1990)
The study concentrated on the maternal and child health activities conducted by the PHM. The performance of the PHM was taken as the dependent variable while the personality characteristics and work environment variables formed the independent variables. The significant independent variables that were found to influence performance of PHMs are age of PHM, ownership of house, number of school going children, distance to the office from the house, the population served, the mode of transport and job satisfaction of the PHMs. Service period in the present area, number of supervisory visits by the supervising public health. Midwife and the husbands income had a significant linear relationship with the performance. The motivational characteristics of the PHM as assessed by their supervising officers, did not correlate well with the performance of the PHMs. The factors that have been identified in this study can be made use of in selection, training and deployment of this category of worker. The monitoring mechanism that was developed at PHM level would from a simple management information flow that would help in the enhancement of work performance of this category of worker by improving supervision and on the job training of individual PHMs